Macroeconomic and capital market determinants of initial public offerings: A Time-series analysis in the Polish capital market - Meluzín, Tomáš; Zinecker, Marek; Meluzínová, Jana (Univerzita Pardubice, 2015)
The main objective of this study is to indicate the influence of local macroeconomic and capital market factors on the values of IPOs in Poland over the period of 2003 to 2012. Our sample includes 330 local enterprises that conducted an IPO on the Main Market of the Warsaw Stock Exchange after Polish EU accession. The models for which estimation results are presented in this paper reveal that the individual country regression analysis working with untransformed IPO values (Model 1) did not generate significant parameter estimates. On the other hand, a logarithmic transformation of IPO values leads to persistently significant estimates for our regressions. Based on the Model (2) the empirical evidence supported the hypothesis that Polish ten-year government bond yields (indicating the price of competing financing funds) have explanatory power for IPO values. However, our assumption that also other macroeconomic- and capital market indicators have explanatory power for IPO values in the Polish capital market could not be supported by empirical evidence.
Keywords: going public; initial public offering; IPO; capital market; macroeconomics; determinants; Poland; E44; G23; G32